Ultrasonic assisted extraction modelling and phytochemicals profiling of bangle rhizome (Zingiber cassumunar Roxb.) - Utama, Niko; Martati, Erryana; Harijono, Harijono (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
Zingiber Cassumunar Roxb., locally known as bangle, has pharmacological activities as an antioxidant, anti-inflammatory, anticancer, neuroprotective, and antibacterial. Green technology extractions have more advantages than conventional extraction. Therefore, this study aims to model the extraction conditions of ultrasound-assisted extraction (UAE) using the Box-Behnken design (BBD) response surface method. Extraction of the bangle was performed using an ultrasonic bath with various bangle-to-ethanol ratios (1:15, 1:30, and 1:45 w/v), ethanol concentrations (60, 70, and 80%), and extraction times (5, 15, and 25 min). The program selected the quadratic model prediction to determine the relationship between bangle-to-ethanol ratio, ethanol concentration, and extraction time on the total phenolics and antioxidant activity. The optimization results showed that the optimum conditions for bangle rhizome extraction were a bangle-to-ethanol ratio of 1:45 w/v, an ethanol concentration of 70%, and an extraction time of 25 min. Under these conditions, total phenolic compounds of 5.48 mg GAE/g and antioxidant activity of 69.18% were obtained. The model had a desirability value of 0.938. The model agreed with the predicted antioxidant activity values (p >0.05). Furthermore, five phenolic group compounds, 11 coumarin group compounds, and 10 alkaloid group compounds were identified using LC-MS/MS QTOF.